The fecal microbiome and serum concentrations of indoxyl sulfate and p‐cresol sulfate in cats with chronic kidney disease. (18th December 2018) - Summers, Stacie C.; Quimby, Jessica M.; Isaiah, Anitha; Suchodolski, Jan S.; Lunghofer, Paul J.; Gustafson, Daniel L.
Abstract : Background: Intestinal dysbiosis has been documented in humans with chronic kidney disease (CKD) and is thought to contribute to production of the uremic toxins indoxyl sulfate (IS) and p‐cresol sulfate (pCS). Characteristics of the fecal microbiome in cats with CKD and correlation to serum concentrations of uremic toxins are unknown. Objectives: To characterize the fecal microbiome and measure serum IS and pCS concentrations of cats with CKD in comparison to healthy older cats. Animals: Thirty client‐owned cats with CKD (International Renal Interest Society stages 2‐4) and 11 older (≥8 years) healthy control cats. Methods: Prospective, cross‐sectional study. Fecal samples were analyzed by sequencing of 16S rRNA genes and Escherichia coli quantitative PCR (qPCR). Serum concentrations of IS and pCS measured using liquid chromatography tandem mass spectrometry. Results: Cats with CKD had significantly decreased fecal bacterial diversity and richness. Escherichia coli qPCR showed no significant difference in bacteria count between control and CKD cats. Cats with stage 2 ( P  = .01) and stages 3 and 4 ( P  = .0006) CKD had significantly higher serum IS concentrations compared to control cats. No significant difference found between stage 2 and stages 3 and 4 CKD. The pCS concentrations were not significantly different between CKD cats and control cats. Conclusions and Clinical Importance: Decreased fecal microbiome diversity and richness is associated with CKD in cats. Indoxyl sulfate concentration is significantly increased with CKD, and cats with stage 2 CKD may suffer from a similar uremic toxin burden as do cats with later stage disease.